2009
DOI: 10.1007/s00779-009-0264-1
|View full text |Cite
|
Sign up to set email alerts
|

Designing playful interactions for social interaction and physical play

Abstract: This paper describes three design values that we apply for designing playful interactions. Interactive play objects can stimulate social interaction and physical play by providing motivating feedback to players' behavior; they can allow players to create their own game goals and rules in an open-ended play context and support social player interaction patterns. This design approach is illustrated by six design cases in which our assumptions were examined in various play contexts. The results show that the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 25 publications
0
112
0
7
Order By: Relevance
“…However, several studies underline the fracturing of physical and virtual spaces, and stress the fact that the children of today have more difficulty in getting into contact with their physical local surroundings and spaces due to the decrease of opportunities for exchanges with them [17,46]. As pointed out by Bekker et al [6], by spending an increasing amount of their time behind their computers, children tend to have a less active life. According to Gauthier and Moukalou [17] the new technologies allow disembodying of the exploration of the world: it happens through the cyberspace where corporal and spatial constraints are removed, so that no physical sensation is associated with it.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies underline the fracturing of physical and virtual spaces, and stress the fact that the children of today have more difficulty in getting into contact with their physical local surroundings and spaces due to the decrease of opportunities for exchanges with them [17,46]. As pointed out by Bekker et al [6], by spending an increasing amount of their time behind their computers, children tend to have a less active life. According to Gauthier and Moukalou [17] the new technologies allow disembodying of the exploration of the world: it happens through the cyberspace where corporal and spatial constraints are removed, so that no physical sensation is associated with it.…”
Section: Introductionmentioning
confidence: 99%
“…Games that encourage activity are also be apt for encouraging social play [15,43,49] and even attract wider user participation [6,29]. With qualitative studies, research has shown that the physicality of game artifacts can contribute to and facilitate social play [2,39]. Though technically the wristbands worn by players in Spellbound are not game artifacts like a ball might be, we believe that, because they communicate information about the state of progress of the other team, they contribute to the sense of togetherness more viscerally than viewing the same information on the smartphone screen.…”
Section: Related Workmentioning
confidence: 99%
“…Here are a few diverse examples: help children deal with bullying situations [10]; motivate people to recycle waste materials [11,12]; encourage children to decrease energy consumption at home [13]; encourage healthy dietary behaviors in kindergarten children [14]; raise teenagers' oral health and dental hygiene awareness [15]; stimulate physical play [16]; help people quit smoking [17]; help elders take their medication on time [18]; improve engagement in science controversies and develop skills in evaluating evidence and forming arguments [19]; improve awareness of drugs abuse effects [20]; raise awareness about water scarcity [21]; improve workers' mental engagement in routine activities [22]; treat cockroach phobia [23]; incentive people to throw rubbish in a bin, instead of on the floor [24]; incentive people to obey the speed limit [25].…”
Section: Changing Behavior With Gamesmentioning
confidence: 99%